Inhibitory effect of Lactobacillus plantarum isolated from the different stages of the porcine meat production chain against Campylobacter coli - Ruiz, M J (Universidad Nacional del Litoral, 2021)
Lactobacillus plantarum has a great capacity to adapt to environmental and have antibacterial capacity against different pathogen. This is a potential alternative for the control of pathogen in food coming slaughter animal. The objective of this work was to determine the antibacterial effect of L. plantarum strains against C. coli strains. L. plantarum LP1, LP3, LP5 and LP7 of porcine origin and a reference strain of Campylobacter coli NCTC 11366 were used. C. coli and L. plantarum was reactivated. Lyophilized ELC and ELCn were obtained. C. coli was distributed on the surface of mCCDA by swab and the ELC and the ELCn were inoculated in wells previously made on the agar. After 48 h, the diameter of the zone of inhibition was measured. The inhibition halos produced were 23.2 mm. The ELCn showed less antagonistic activity. The LP5 ELC generated higher inhibition halos and ELCn showed no differences between the four strains studied. L. plantarum strains, isolated from the pig production chain, could potentially be applied to control C. coli. This data is added to the scarce scientific evidence of the inhibitory effect of L. plantarum before this zoonotic pathogen of importance in public health.